Pensions and Contemporary Socioeconomic Change - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 2001)
The paper discusses the consequences for the functioning of different pension systems of various types of socioeconomic changes, mainly demographic developments, variations in productivity growth and changes in real interest rates. Two of the pension systems have exogenous and four have endogenous contributions rates. I analyze both marginal and radical pension reforms for the purpose of making pension systems more stable, avoiding arbitrary redistributions between generations and dealing with increased heterogeneity of the population in terms of family structure and international mobility. The advantages of combining PAYGO and actuarially fair systems are pointed out.
Keywords: H55; 330; Pension Reforms; Social Economic Change; Redistribution among Generations; Gesetzliche Rentenversicherung; Rentenfinanzierung; Bevölkerungsentwicklung; Einkommensverteilung; Theorie